Thermoplastic Starch Nanocomposites Reinforced with Cellulose Nanocrystal Suspensions Containing Residual Salt from Neutralization. Issue 8 (29th May 2021) - Metzger, Christoph; Briesen, Heiko
Abstract: Sulfuric acid‐catalyzed hydrolysis of cellulose commonly isolates cellulose nanocrystals (CNCs). Neutralizing the reactant solution with sodium hydroxide facilitates efficient downstream processing, but residual salt remains in the product. This study examines the reinforcing effects of CNCs from suspensions that contain residual salt on the mechanical properties of thermoplastic starch nanocomposites. By reinforcing starch films with up to 5 wt% CNCs, stiffness and strength are improved by 118% and 79%, respectively, indicating a good dispersion of CNCs in the starch matrix. Compared to nanocomposites incorporating salt‐free CNCs, the remaining salt has no significant impact on the material's mechanical performance. The results indicate great potential of CNCs containing residual salt as biobased, low‐cost nanofiller in hydrophilic polymer matrices. Abstract : Cellulose nanocrystals (CNCs) are biobased nanoparticles with high mechanical strength. They are produced by hydrolysis and subsequent dialysis to remove residual acid. Alternatively, the acid can be neutralized, which facilitates faster processing and less water consumption, but then a salt fraction remains. CNCs containing residual salt enables equivalent performance as reinforcing filler in thermoplastic starch films compared to salt‐free CNCs.